(untitled) (Global Journal of Management and Business Research, 2014)
The utilization of energy from fossil fuels has becoming important driver and plays a vital rolefor all the economies. The alternative resources have wider concerns over the issues of energy security and sustainable development in the sector. In this context, for meeting the national power deficit and addition to thermal power generation capacity, power generation from thermal plants has been a very important history of the Indian power sector.